STRATEGI PEMBELAJARAN UNTUK MENGEMBANGKAN SIKAP YANG MENGHARGAI MULTIKULTURAL - Sofiana Eka Putri; Savira Dwi Nastitiana; Deni Setyawan; Ahmad Manshur (STKIP Subang, 2026)
This study is grounded in the urgency of implementing multicultural education within the learning process as a response to cultural, ethnic, and religious diversity in educational settings. The objective of this research is to analyze effective learning strategies in internalizing multicultural values in schools. The research employs a qualitative approach through library research by reviewing relevant scholarly literature. The findings indicate that multicultural education is oriented toward fostering tolerance, appreciation of plurality, and the development of civilized student character. The implementation of learning strategies such as discussion, simulation, role-playing, cooperative learning, value analysis, and social analysis has proven effective in encouraging active student participation and enhancing awareness of diversity. Furthermore, teachers play a crucial role in establishing a democratic, inclusive, and non-discriminatory learning environment. The selection of instructional strategies should consider learning objectives, student characteristics, and the socio-cultural context. The study concludes that the appropriate implementation of multicultural learning strategies can improve the quality of the learning process and cultivate students who demonstrate empathy, tolerance, and respect for diversity. It is therefore recommended that educators continuously enhance their professional competencies in applying multicultural-based learning strategies.